Development of superposition-based quantum key distribution protocol in decentralized full mesh networks - Begimbayeva, Yenlik; Ussatova, Olga; Zhaxalykov, Temirlan; Akhtanov, Amir; Pashkevich, Ruslan; Arshidinova, Mukaddas (Eastern-European Journal of Enterprise Technologies, 2024)
The object of this research is the security of communication networks, particularly in decentralized, multi-user environments where robust data protection and integrity are critical. The issue under discussion is the rising vulnerability of conventional cryptography systems resulting from ever complex cyberattacks and the expected risks presented by quantum computing possibilities. The development of a QKD protocol employing quantum superposition to improve data security and resilience against both present and future quantum-based cyber-attacks is demonstrated by the achieved results of this work. Achieving scalability and autonomous eavesdropping detection, this protocol lets several communication nodes securely exchange randomly produced keys without centralized management. A quick analysis of the results reveals that main elements influencing the great durability, security, and adaptability of the protocol are quantum superposition and its distributed character. Without centralized authority, the characteristics of the obtained results – especially the use of optical components, detectors, and quantum sources in conjunction with classical communication channels – solve the problem of ensuring data confidentiality and integrity in a multi-user environment. This protocol’s practical reach covers safe communication applications in both public and private sectors, therefore addressing situations calling for strong data protection against modern cyberattacks. Conditions for practical application include settings like government, financial, or health-related interactions when safe information flow is crucial. This QKD system offers a future-ready security solution for high-stakes environments and represents notable advancement toward protecting data from quantum and conventional attacks